Att explicitgöra det implicit sagda — i självmordsnära kvinnors tal om offerskap, kön och sexualiserat våld (Sociologisk Forskning, 2003)
With this text I want to shed light upon the relationship between womens suicidal thoughts and acts and their experiences of sexualised violence. The main focus is set on how experiences of sexualised violence connects to patterns of victimization, and how this complicated interrelation interweave in the ways women think and act in regard to suicide. The initiating question is: “What can it mean to think of oneself in terms of victimhood when one has experiences of sexualised violence?”. My point of departure is to listen to and highlight how abused women themselves describe and interpret their suicidal acts. An analysis of how the women expresses their experiences is made, where I try to make explicit underlying (implicit) cultural notions of victims and offenders. I then search for indications on how to comprehend this silently gendered phenomena. Overall, I try to develop a frame of interpretation that can make these womens voices explicable.
Keywords: suicidal behaviours; sexualised violence; gender; victimhood